Dynamic analysis and optimal control of a stochastic information spreading model considering super-spreader and implicit exposer with random parametric perturbations - Kang, Sida; Hou, Xilin; Hu, Yuhan; Liu, Hongyu (Frontiers in Physics, 2023)
Environmental factors in social systems affect information spreading at all times. This paper proposes a stochastic S2EIR model that considers the presence of super-spreaders and implicit exposers in information spreading as well as the stochastic perturbation of model parameters. The existence of a global positive solution is then demonstrated. Sufficient conditions for information disappearance and smooth distribution of information are calculated. Furthermore, the optimal control strategy for the stochastic model is proposed. The results of the theoretical analysis are supported by numerical simulations and compared to the parameter variations of the deterministic model. The results of this study indicate that white noise facilitates the spread of information. The intensity of perturbation is proportional to the fluctuation of information spreading. Controlling random parameters can effectively facilitate the spread of information.